A Game-Theoretic View of the Fiscal Theory of the Price Level - Bassetto, Marco (Econometrica, 2002)
The goal of this paper is to probe the validity of the fiscal theory of the price level by modeling explicitly the market structure in which households and the governments make their decisions. I describe the economy as a game, and I am thus able to state precisely the consequences of actions that are out of the equilibrium path. I show that there exist government strategies that lead to a version of the fiscal theory, in which the price level is determined by fiscal variables alone. However, these strategies are more complex than the simple budgetary rules usually associated with the fiscal theory, and the government budget constraint cannot be merely viewed as an equilibrium condition.